Sustainability of Swiss fiscal policy - Gebhard Kirchgässner; Silika Prohl (Center for Economic Studies and ifo Institute (CESifo), 2006)
We examine whether Swiss federal fiscal policy was sustainable over the period from 1900 to 2002. We perform unit root and cointegration tests for federal revenues and expenditures, taking into account a structural shift in the budgetary process related to World War II. We find sustainability over the entire period. However, splitting the sample into two sub-samples before and after World War II, the results do much less support sustainability. Finally, applying the tax smoothing model of BARRO (1979), we show that cyclical fluctuations of the output and changes in expected inflation rate are major determinants of the federal budget deficit over the time period considered.
Keywords: H63; H62; 330; sustainability; budget deficit; cointegration; structural breaks; Antizyklische Finanzpolitik; Haushaltsdefizit; Haushaltskonsolidierung; Schätzung; Schweiz